2017
DOI: 10.1016/j.gaceta.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an intervention to improve diabetes self-management on clinical outcomes in patients with low educational level

Abstract: In this pragmatic study, a simple and inexpensive intervention delivered in primary care showed a modest benefit in glycaemic control compared with usual care, although no effect was observed in the secondary outcomes. Further research is needed to design and assess interventions to promote diabetes self-management in socially vulnerable patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
9
0
5
Order By: Relevance
“…These results are consistent with previous similar studies conducted among diabetic patients in other countries [15][16][17][18][19] and suggest that nutrition education can be effective in helping these patients with their condition. Several studies have explored the efficiency of different interventions aiming at improving the management of diabetes, especially in vulnerable populations 20,21 and despite the difference in the approaches, they observed a decreasing Hb1Ac.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous similar studies conducted among diabetic patients in other countries [15][16][17][18][19] and suggest that nutrition education can be effective in helping these patients with their condition. Several studies have explored the efficiency of different interventions aiming at improving the management of diabetes, especially in vulnerable populations 20,21 and despite the difference in the approaches, they observed a decreasing Hb1Ac.…”
Section: Discussionsupporting
confidence: 93%
“…pain intensity, level of fatigue and use of pain medication). Seventeen studies targeting diabetes reported mean changes in HbA1c, with seven reporting significant improvements in the intervention compared to usual care [42, 46, 47, 50, 52, 53, 56, 109, 112]. Goudswaard et al [42] reported a decrease in HbA1c at six weeks by 0.7% more (95% CI 0.1, 1.4) in those receiving the intervention when compared with control.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies included in this review are summarised in online supplemental table 1. The studies were conducted in the USA (n=13, 76.5%), [31][32][33][34][35][36][37][38][39][40][41][42][43] the UK (n=2), 44 45 Spain (n=1) 46 and the Netherlands (n=1). 47 Eight studies were conducted among migrants of European, Caucasian, American, Mexican or Middle East background, 31-35 40 41 46 five among those of black and African backgrounds 36-39 42 and four 43-45 47 among South Asian migrants.…”
Section: Participants Characteristics and Study Designsmentioning
confidence: 99%